Context Boards in the Teaching Foreign Languages and Philological Disciplines (Proceedings of the International Conference on Future of Education, 2021)
: Developing modern technologies in the education sector requires brand new decisions toimprove the proceeding and memorise information. The accelerated study rate reduces the amount ofconcentration and accessible time, so an average student experiences difficulty gathering knowledgeand required skills. When placed in such conditions, students and teachers find extraordinarymethods for lessons and exercises to simplify acquiring knowledge and fulfilling all the tasks. TheContext Board represents the specified topics and provides the ability to disclose a sufficient level ofknowledge appropriately. The mentioned draft is based on different ways of memorising and populartechnical capacity. The main purpose of this study is to determine the optimal method of the materialpresentation within the framework of the developed project. The experiments have shown the overalleffectiveness of the context boards. The method itself takes into consideration the features of personswith different types of information perception. It is also essential that organising the specified andrequested topics allows to systematise information and realise all the significant connections betweendifferent subjects and choose the study format.
Keywords: context board; educational technology; thematic board; memorisation techniques